Kredibilitas Influencer Dalam Mempromosikan Produk MakeOver Cosmetics Di Kalangan Mahasiswa - Avirley Nursyafa Baluci; Irdan Fattur Mi’raj; Abiyasa Dwi Putra; Budiana Ruslan (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2021)
Abstract: The credibility of social media-based influencers has become an important factor in consumer decision making. The study aimed of this study was to see how the influencers' credibility in MakeOver Cosmetics products among students was. The research sample was taken as many as 91 student respondents from the Faculty of Communication Sciences, Islamic University of Bandung. The research method used in this study is an explanation that serves to impact the influencer credibility (IC) felt by consumers, using a credibility model of the dimensions of Attractiveness, Expertise, and Trustworthiness. The software used to measure the constructed model in SmartPLS 3.3.2. The results showed that the Composite Reliability on the credibility of the influencers was 0.943 accepted. R. Square in the influencer's credibility to the dimensions studied is attractiveness is 0.737, and Expertise is 0.886 and Trustworthiness is 0.804. So, this dimension can be said that the influencer's credibility is significant. While the Average Variance Extracted (AVE) given by the credibility of the influencer is 0.548 a statement that the construct is accepted. The development of research on the credibility of influencers still has much to be researched in the future.